Training Motivation of Football Player Solok Fc - Niki Candra Putra; Wilda Welis (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
The problem of this research is that the writer wants to see a picture of how much motivation the Solok FC soccer athletes have won the 3rd league PSSI. The author is interested in digging deeper into what factors make Solok FC a winner in the hunt for one ticket for league 3 in the Sumatran region. This research is a descriptive study. This research was conducted at Solok FC soccer field. Data retrieval was carried out on October 10, 2018. The study population was all 26 athletes from solok FC. The sampling technique was carried out with a total sampling technique of 26 people. The results of the analysis show that: 1) The motivation level of solok FC soccer athletes is 84.58% with very high qualifications; 2) The level of achievement of the intrinsic motivation of solok FC soccer athletes is 87.02% in very high qualifications; 3) The level of achievement of the extrinsic motivation of solok FC soccer athletes is 82.28%. with very high qualifications Abstrak Masalah dari penelitian ini adalah bahwa penulis ingin melihat gambaran seberapa besar motivasi atlet sepakbola Solok FC telah memenangkan PSSI liga ke-3. Penulis tertarik untuk menggali lebih dalam faktor-faktor apa yang membuat Solok FC menjadi pemenang dalam perburuan satu tiket untuk liga 3 di wilayah Sumatera. Penelitian ini adalah penelitian deskriptif. Penelitian ini dilakukan di lapangan sepak bola Solok FC. Pengambilan data dilakukan pada 10 Oktober 2018. Populasi penelitian adalah semua 26 atlet dari solok FC. Teknik pengambilan sampel dilakukan dengan teknik total sampling sebanyak 26 orang. Hasil analisis menunjukkan bahwa: 1) Tingkat motivasi atlet sepakbola FC solok adalah 84,58% dengan kualifikasi sangat tinggi; 2) Tingkat pencapaian motivasi intrinsik atlet sepakbola FC solok adalah 87,02% dalam kualifikasi yang sangat tinggi; 3) Tingkat pencapaian motivasi ekstrinsik atlet sepakbola FC solok adalah 82,28%. dengan kualifikasi sangat tinggi.